Primary alveolar rhabdomyosarcoma of the breast skin: a case report and literature review - V. S. Surkova; N. N. Volchenko; E. A. Nikitina; E. A. Troshenkov; A. M. Lavrova; G. G. Khakimova (ABV-press, 2022)
Alveolar rhabdomyosarcoma is one of the four subtypes of rhabdomyosarcoma identified by the World Health Organization. This type of malignant neoplasms more often affects deep soft tissues of extremities and occurs in young ages, regardless of gender. According to the medical literature, no more than 45 cases of the development of primary cutaneous rhabdomyosarcoma have been reported in the world. In this report, we describe a clinical case of a 40-year-old woman with primary localization of alveolar radbomyosarcoma in the skin of the mammary gland.